Abnormal Elasticity of Single-Crystal Magnesiosiderite across the Spin Transition in Earth's Lower Mantle - Fu, Suyu; Yang, Jing; Lin, Jung-Fu (Physical review letters, 2017)
Brillouin light scattering and impulsive stimulated light scattering have been used to determine the full elastic constants of magnesiosiderite [(Mg_{0.35}Fe_{0.65})CO_{3}] up to 70 GPa at room temperature in a diamond-anvil cell. Drastic softening in C_{11}, C_{33}, C_{12}, and C_{13} elastic moduli associated with the compressive stress component and stiffening in C_{44} and C_{14} moduli associated with the shear stress component are observed to occur within the spin transition between ∼42.4 and ∼46.5  GPa. Negative values of C_{12} and C_{13} are also observed within the spin transition region. The Born criteria constants for the crystal remain positive within the spin transition, indicating that the mixed-spin state remains mechanically stable. Significant auxeticity can be related to the electronic spin transition-induced elastic anomalies based on the analysis of Poisson's ratio. These elastic anomalies are explained using a thermoelastic model for the rhombohedral system. Finally, we conclude that mixed-spin state ferromagnesite, which is potentially a major deep-carbon carrier, is expected to exhibit abnormal elasticity, including a negative Poisson's ratio of -0.6 and drastically reduced V_{P} by 10%, in Earth's midlower mantle.